Common Best Proximity Point Theorems in JS-Metric Spaces Endowed with Graphs. (11th May 2021) - Thangthong, Chaiporn; Charoensawan, Phakdi; Dangskul, Supreedee; Phudolsitthiphat, Narawadee
Abstract : In this paper, we introduce a notion of G -proximal edge preserving and dominating G -proximal Geraghty for a pair of mappings, which will be used to present some existence and uniqueness results for common best proximity points. Here, the mappings are defined on subsets of a JS-metric space endowed with a directed graph. An example is also provided to support the results. Moreover, we apply our result to a similar setting, where the JS-metric space is endowed with a binary relation.